Maternal Morbidity And Mortality Patterns in Uttar Pradesh - Nandan Deoke; Saxena Badri N (Wolters Kluwer Medknow Publications, 1997)
Research question: What is the extent of maternal morbidity and mortality in the community? Objectives: To know the extent and pattern of maternal mortality in the community. Study area: The districts of Uttar Pradesh namely Agra and Farrukhabad, covering 206 villages in 15 blocks. Sample Size: 51, 186 households and 292,496 population. Participants: Married women in reproductive age group. Setting: Rural community Development Blocks. Study variables: Menstrual problems, gynaecological problems, general morbidity and maternal deaths. Outcome variables: Maternal morbidity and mortality. Study Design: Community based cross- sectional study. Analysis: Simple proportions. Results: Over 47.5% of women reported excessive discharge, 15-16% complained of foul smelling discharge besides other problems like urinary infections, incontinence, prolapse, vesico-vaginal fistula etc. Around 22-27% of women suffered general morbidity, predominant being fever/cough/cold, malaria, diarrhoea and anemiaâ€s. Overall, high level of (703 per 100,000) maternal mortality was reported in the area. Respective fingers for Agra and Farrukhabad being 582 and 992 per lakh live births. Over 50% of these deaths occurred at home, 22% in government hospitals, 12% in private hospitals and 15% in transit. Leading causes of maternal mortality were; haemorrhage, retained placenta, sepsis, anemia, jaundice and tetanus.